1972
DOI: 10.1063/1.1678019
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Excitation of Vacuum Ultraviolet Emission Features by Electron Impact on Molecular Gases. III. CO2

Abstract: Vacuum ultraviolet multiplets of Cr, Cn, and Or have been produced by electron impact on CO 2 . Absolute emission cross sections for these multiplets have been measured from threshold to 350 eV. The electrostatically focussed electron gun used in this series of experiments is described in detail. The atomic multiplets which were produced by dissociative excitation of CO2 and the cross sections at 100 eV are: Or (2p' 3p_ 2p 3 3s 3S) 1304 A-1.04X10--18 cm 2 ±18%; Cr(2s 2 2p2 3P-2s2p3 3PO) 1329 A-2.67XlO-19 cm 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

1973
1973
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 17 publications
4
28
0
Order By: Relevance
“…3. Both spectra in this figure show weak C i multiplets whose relative intensities suggest electron impact dissociation of CO 2 (Ajello 1971b;Mumma et al 1972). However, electron impact dissociation of CO 2 has a considerably smaller cross section for the production of the CO bands than for C i λ1657 (Mumma et al 1971) and so the absence of CO emission in the left panel suggests that the observed emission in the right panel is due to solar resonance fluorescence.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…3. Both spectra in this figure show weak C i multiplets whose relative intensities suggest electron impact dissociation of CO 2 (Ajello 1971b;Mumma et al 1972). However, electron impact dissociation of CO 2 has a considerably smaller cross section for the production of the CO bands than for C i λ1657 (Mumma et al 1971) and so the absence of CO emission in the left panel suggests that the observed emission in the right panel is due to solar resonance fluorescence.…”
Section: Discussionmentioning
confidence: 86%
“…We can exclude prompt photodissociation of H 2 O based on both the low photodissociation rate (Wu & Chen 1993) and the selection rules for H 2 O absorption (Wu & Judge 1988). Electron impact on CO 2 is the likely source of the weak C i λλ1561 and 1657 multiplets and the very weak C ii λ1335 multiplet (Ajello 1971a,b;Mumma et al 1972). The source of the electrons is photoionization of H 2 O and the resultant photoelectrons have peak energies in the range of 25 to 50 eV, although more energetic electrons have also been detected by the Ion and Electron Sensor (IES) instrument on Rosetta (Burch, priv.…”
Section: September Observationsmentioning
confidence: 99%
“…2. The electron impact excitation functions fall off relatively slowly at high energies; this indicates that the initial excitation in this energy region is a dipole-allowed transition [Mumma et al, 1971a]. However, the excitation functions for CO(A, v' = 0, 1) (and possibly v' = 4) exhibit sharp early peaks near 30 eV.…”
Section: Their Instrumental Wavelength Resolution (• 10/•) Was Too Lowmentioning
confidence: 96%
“…The measured energy dependence of the aA/an ratio is the same in both experiments[Zipf, 1985a, b]. for this process has been used as a calibration standard by Mumrna andZipf [1971] and byStone and Zipf [1974] Shemansky et al [1985],. Van Zyl et al…”
mentioning
confidence: 99%